Minimally invasive Dega acetabuloplasty for the treatment of neuromuscular hip dysplasia. Issue 4 (July 2018) - Kappa, Jason E.; Shore, Benjamin J.; Allar, Benjamin G.; Bruce, Robert W.; Fletcher, Nicholas D.
Abstract : Background: Dega acetabuloplasty is used in the management of neuromuscular hip dysplasia. A minimally invasive technique may decrease perioperative morbidity while allowing for adequate reduction and ensuring stability. We sought to determine the impact of a minimally invasive Dega acetabuloplasty (MID) on hip stability after neuromuscular hip reconstructions. Methods: A retrospective review was performed of consecutive patients with cerebral palsy (GMFCS IV/V) and neuromuscular hip dysplasia undergoing bony reconstruction including a varus derotational osteotomy (VDRO) of the femur and a Dega acetabuloplasty. Clinical records were reviewed to evaluate preoperative comordibities and clinical complications. Review of pelvic radiographs preoperatively and at follow-up evaluated correction of acetabular index, migration percentage, and the presence of an intact Shenton's arc. Results: Forty-two patients (45 hips) underwent MID surgery as part of a reconstructive approach for neuromuscular hip subluxation or dislocation. Preoperative migration percentage averaged 61.1±4.0% (range, 39-100%). In addition to bony reconstructions, 91.4% of hips had soft-tissue balancing. Patients had an average estimated blood loss of 102±69.9 cc, mean operative time of 165±44 min, and an average length of stay of 3.2±1.3 days. No patient required reoperation. Operative intervention resulted in a mean migration percentage of 12.1%±2.5 and residual acetabular index of 16.0±8.7 degrees with 84.4% (38 of 45) of hips having an intact Shenton's arc at 1-year of follow-up. Conclusions: The MID provides acceptable rates of postoperative hip stability at 1 yr with low blood loss, surgical time, length of stay, and postoperative medical complications. Level of Evidence: Level IV.